LEMBAGA PENDIDIKAN SEKOLAH DAN MADRASAH (Pembaharuan Metode dan Sistem Pendidikannya) - Aminuddin Aminuddin; Bahaking Rama; Andi Achruh (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The existence of schools and madrasas has created a dichotomy between "religious" science and "general" science. Schools are perceived as "educational institutions that organize general science education", organized and managed by the Ministry of National Education. Meanwhile, madrasas are perceived as "institutions that organize religious education" organized and managed by the Ministry of Religion. From these two schools, the perception emerged that schools managed by the National Education Office were perceived as "public", non-religious, or "secular" schools, but advanced, foremost, and modern. Meanwhile, schools managed by the Ministry of Religion are perceived as "religious" and religious schools, but are left behind, closed to the progress of science and technology, and traditional. Maybe that perception is not entirely correct, and also not entirely wrong. On the one hand, there are schools managed by the National Education Office which are still underdeveloped, traditional and slum; and on the other hand, there are modern, international standard, and advanced Islamic schools. This dichotomy still cannot be eliminated, but it needs to be mediated and converged, so that religion and science and technology are taught, mastered, and applied by every student. The level of the concept of dichotomy will lead to educational dulaism at the practical level which in turn will lead to a decline in educational outcomes. It is important to note that what is needed now in efforts to improve the quality of formal education is to improve the quality of the system. In this case, what is meant by a system is a set of educational plans, processes and evaluations that are built on Islamic values.